Reducing Status Quo Bias in Choice Experiments – An Application of a Protest Reduction Entreaty - Ole Bonnichsen; Jacob Ladenburg (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2010)
In stated preference literature, the tendency to choose the alternative representing the status quo situation seems to exceed real life status quo effects. Accordingly, status quo bias can be a problem. In Choice Experiments, status quo bias is found to be strongly correlated with protest attitudes toward the cost attribute. If economic values are to be elicited, this problem is difficult to remedy. In a split sample framework we test a novel ex-ante entreaty aimed specifically at the cost attribute and find that it effectively reduces status quo bias and improves the internal validity of the hypothetical preferences.
Keywords: C10; C51; C52; C90; 330; Choice Experiment; Status Quo Bias; Entreaty; Stated Preference